Resíduos agroindustriais como fonte de silício para a cultura do milho - Lima, Paulo Henrique de (2012)
The agro-industrial residues have great potential for providing silicon (Si) and other nutrients for crops. The objective of this work to assess the supply of silicon for organic waste agribusiness, and to evaluate the influence of this nutrient in the accumulation of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg ) and sulfur (S) in maize. We analyzed the accumulation of silicon in the leaves and stems of the plant and the effect of these sources in stem diameter, the height and mass of dry corn plant, as well as the accumulation of N, P, K, Ca, Mg and S in corn leaves provided by agro-industrial residues and by levels of silicon used. The experiment was conducted in a greenhouse in a completely randomized design (4x3) + 1. We evaluated three sources organic agribusiness (bagasse ash from sugar cane filter cake rotary sugarcane and rice hulls), and for the supply of silicon also evaluated the mineral source (calcium silicate PA); three strengths of SiO2 (175 kg ha-1, 350 kg ha-1 and 700 kg ha-1) and additional treatment (control), which received no SiO2. The sources and doses of SiO2 did not affect the mass of dried corn plants. However, the addition of SiO2 dose provided an increase in the diameter of stem of the maize plant. The rice hulls was more efficient among all treatments in Si supply to the corn crop. The supply of Si favors the absorption and consequent accumulation of potassium and phosphorus from the corn plant. There was no relationship between the supply of Si and Mg and S uptake by corn plant. Finally, there was no relationship between the accumulation of Si and the reduction of leaf N in corn plants.